DNA barcoding fishes from the Congo and the Lower Guinean provinces: Assembling a reference library for poorly inventoried fauna. (17th April 2019) - Sonet, Gontran; Snoeks, Jos; Nagy, Zoltán T.; Vreven, Emmanuel; Boden, Gert; Breman, Floris C.; Decru, Eva; Hanssens, Mark; Ibala Zamba, Armel; Jordaens, Kurt; Mamonekene, Victor; Musschoot, Tobias; et al.
Abstract: The Congolese and Lower Guinean ichthyological provinces are understudied hotspots of the global fish diversity. Here, we barcoded 741 specimens from the Lower and Middle Congo River and from three major drainage basins of the Lower Guinean ichthyological province, Kouilou‐Niari, Nyanga and Ogowe. We identified 194 morphospecies belonging to 82 genera and 25 families. Most morphospecies (92.8%) corresponded to distinct clusters of DNA barcodes. Of the four morphospecies present in both neighbouring ichthyological provinces, only one showed DNA barcode divergence <2.5%. A small fraction of the fishes barcoded here (12.9% of the morphospecies and 16.1% of the barcode clusters representing putative species) were also barcoded in a previous large‐scale DNA analysis of freshwater fishes of the Lower Congo published in 2011 (191 specimens, 102 morphospecies). We compared species assignments before and after taxonomic updates and across studies performed by independent research teams and observed that most cases of inconsistent species assignments were due to unknown diversity (undescribed species and unknown intraspecific variation). Our results report more than 17 putative new species and show that DNA barcode data provide a measure of genetic variability that facilitates the inventory of underexplored ichthyofaunae. However, taxonomic scrutiny, associated with revisions and new species descriptions, is indispensable to delimit species and build a coherent reference library.